2021
DOI: 10.1007/s10856-021-06543-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ionizing radiation on surface properties of current restorative dental materials

Abstract: To investigate the impact of radiotherapy on surface properties of restorative dental materials. A conventional resin composite—CRC (Aura Enamel), a bulk-fill resin composite—BFRC (Aura Bulk-fill), a conventional glass ionomer cement—CGIC (Riva self cure), and a resin-modified glass ionomer cement—RMGIC (Riva light cure) were tested. Forty disc-shaped samples from each material (8 mm diameter × 2 mm thickness) (n = 10) were produced according to manufacturer directions and then stored in water distilled for 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…Therefore, they questioned the notion that the increase in MH was due to improved polymerization and suggested that some other, unidentified structural change may be responsible for this effect [ 33 ]. Another explanation for the increase in MH due to radiotherapy was provided by de Amorim et al, who demonstrated, in a scanning electron microscopy study, that radiation can damage the resin-rich layer on the material surface, thereby exposing more inorganic filler particles and, in turn, improving MH [ 34 ]. Their study showed that the same effect can work in the opposite direction to reduce the MH of conventional glass ionomers covered with a coating resin, since in this case, the exposed underlying material is softer than the coating resin damaged by radiation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, they questioned the notion that the increase in MH was due to improved polymerization and suggested that some other, unidentified structural change may be responsible for this effect [ 33 ]. Another explanation for the increase in MH due to radiotherapy was provided by de Amorim et al, who demonstrated, in a scanning electron microscopy study, that radiation can damage the resin-rich layer on the material surface, thereby exposing more inorganic filler particles and, in turn, improving MH [ 34 ]. Their study showed that the same effect can work in the opposite direction to reduce the MH of conventional glass ionomers covered with a coating resin, since in this case, the exposed underlying material is softer than the coating resin damaged by radiation.…”
Section: Resultsmentioning
confidence: 99%
“…The potential of radiotherapy to affect the surface roughness of restorative materials is unclear, as the available literature provides mixed results. A scanning electron microscopy study by de Amorim et al, demonstrated that radiation can expose filler particles in subsurface layers of resin composites and even remove the coating resin layer of glass ionomers, resulting in surface roughening which depends on the size of the exposed particles [ 34 ]. The effect of radiation on surface roughness appears to be material-dependent, as in one study, an increase in Ra was observed only for a resin-modified glass ionomer, while no significant Ra change was observed for conventional glass ionomers and resin composites [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the results suggest that in cases of the need to apply pit and ssure sealants in patients who are going to undergo or have undergone radiotherapy, resin sealants would be the materials of choice because they are not altered by radiotherapy and present a better performance in terms of adherence [29,35,36,38] . However, both classes of materials, resinous and ionomeric, are effective in preventing or paralyzing a carious lesion process, so the material that best ts the speci cations of each patient and the conditions of the operative eld should be chosen, considering the indications and contraindications of the materials [17,35,36,38,46,47,59] .…”
Section: Discussionmentioning
confidence: 99%
“…Through hydrolysis, X groups transform to the alkoxy group and create covalent or hydrogen bonding together with the alkoxy group exist on the inorganic ller particles' surface while Y is reactive groups that attach with organic monomers and therefore enhance adhesion of ller-matrix interface [18] . According to De Amorim et al [19] silanized ouroaluminosilicate llers and methacrylate monomers produced a more stable bond between llers and monomers in resin modi ed glass ionomer, thus post radiation morphology was conserved.…”
Section: Discussionmentioning
confidence: 99%